The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/eat.23666
|View full text |Cite
|
Sign up to set email alerts
|

Reporting racial and ethnic diversity in eating disorder research over the past 20 years

Abstract: Objective: Recent public awareness of racial and ethnic disparities has again brought to light issues of diversity, equity, and inclusion in the eating disorders field. However, empirical information on racial and ethnic representation in eating disorders research is limited, making it difficult to understand where improvements are needed. Method: This study reviewed all studies including human participants published in the International Journal of Eating Disorders in 2000, 2010, and 2020. Differences in likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…Slightly over half of the studies overall reported full race/ethnicity data, and a quarter reported none. Consistent with Egbert et al (2022), reporting of race/ethnicity data increased over time. Yet, 10% of studies published in the last decade did not report race or ethnicity and 20% reported only % White, non-White, or minority.…”
Section: Race/ethnicitymentioning
confidence: 54%
See 3 more Smart Citations
“…Slightly over half of the studies overall reported full race/ethnicity data, and a quarter reported none. Consistent with Egbert et al (2022), reporting of race/ethnicity data increased over time. Yet, 10% of studies published in the last decade did not report race or ethnicity and 20% reported only % White, non-White, or minority.…”
Section: Race/ethnicitymentioning
confidence: 54%
“…A recent review of all articles published in the International Journal of Eating Disorders in the years 2000, 2010, and 2020 found that although racial/ethnic data reporting increased over time, the substantial majority of participants were White (Egbert et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Invariance indicates that the same underlying construct is being measured across groups, and that observed group differences are meaningful, and not the result of measurement error or item bias (B. M. Byrne et al, 2009;Chen, 2008;Putnick & Bornstein, 2016). Because men and marginalized racial/ethnic groups are underrepresented in the ED literature (Egbert et al, 2022;Goel, Jennings Mathis, et al, 2022;Murray et al, 2017), it is important not only to identify the appropriate factor structure for the EDE-Q in men, but also to ensure it is measuring the same constructs across racial and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%